2023
DOI: 10.1038/s43247-023-00679-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerial transport of bacteria by dust plumes in the Eastern Mediterranean revealed by complementary rRNA/rRNA-gene sequencing

Abstract: Processes influencing the transport of airborne bacterial communities in the atmosphere are poorly understood. Here, we report comprehensive and quantitative evidence of the key factors influencing the transport of airborne bacterial communities by dust plumes in the Eastern Mediterranean. We extracted DNA and RNA from size-resolved aerosols sampled from air masses of different origins, followed by qPCR and high-throughput amplicon sequencing of 16 S ribosomal RNA gene and transcripts. We find that airborne ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Notably, DE‐II displayed significant day/night wind speed differences (7.78 m/s vs. 3.38 m/s, respectively). Wind speed has been previously linked with dust generation and bacteria transportation (Erkorkmaz et al, 2023 ; Fujiyoshi et al, 2017 ; Sorkheh et al, 2022 ; Ulrich, 2021 ), possibly associated with the observed microbial richness variation during this event, showing higher values for the daytime samples (see Table 1 , Chao1 and abundance‐based coverage estimator [ACE] values).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Notably, DE‐II displayed significant day/night wind speed differences (7.78 m/s vs. 3.38 m/s, respectively). Wind speed has been previously linked with dust generation and bacteria transportation (Erkorkmaz et al, 2023 ; Fujiyoshi et al, 2017 ; Sorkheh et al, 2022 ; Ulrich, 2021 ), possibly associated with the observed microbial richness variation during this event, showing higher values for the daytime samples (see Table 1 , Chao1 and abundance‐based coverage estimator [ACE] values).…”
Section: Resultsmentioning
confidence: 83%
“…The particulate load has been linked with an increase in microbial richness (Erkorkmaz et al, 2023 ). A similar pattern was observed in our study, showing positive relations between higher PM concentrations (observed in DE_II and DE_III) and richness parameters (Chao1 and ACE values; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Israel has varying airborne microbiomes that depend on air mass, and Gat et al (Gat et al, 2017;Gat et al, 2021;Erkorkmaz et al, 2023;Peng et al, 2021) have measured a variety of desert-and soil-associated bacteria and fungi in air masses that passed over the Nile Delta and the Arabian Peninsula, with some of the latter cases also containing agricultural soil bacteria. Samples from days with no dust events mostly contained bacteria assoc iated with human activity.…”
mentioning
confidence: 99%